2022
DOI: 10.1080/00224499.2022.2042477
|View full text |Cite
|
Sign up to set email alerts
|

Gender Scripts and Female Sexual Functioning: The Role of Sexual Pressure and Sexual Subjectivity

Abstract: Building upon previous research that has already established a negative association between gender scripts' endorsement and female sexual functioning, the present study tested a model that explains how gender scripts' endorsement may affect female sexual functioning through perceived sexual pressure, compliance with unwanted sex, and sexual subjectivity. A community sample of 390 women (mean age = 23.98 ± 4 years; age range: 18-35 years) completed measures of gender scripts' endorsement, sexual pressure, sexua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 62 publications
0
8
0
Order By: Relevance
“…Some of the research on UCS, however, does point to negative correlates of consenting to unwanted sex and highlights the importance of better understanding vulnerability factors associated with UCS. Among a sample of Italian heterosexual women, Scappini and Fioravanti (2022) found that the frequency of UCS was negatively correlated with sexual functioning and positively correlated with depression and anxiety. In a U.S. sample of individuals who identified as lesbian, gay, bisexual, transgender, or queer, who were in polyamorous relationships, and/or who were practitioners of bondage, domination, and sadomasochism (BDSM), Rubinsky (2020) found that engaging in UCS in the current relationship was negatively associated with mental health in the past 30 days.…”
Section: Why Ucs Mattersmentioning
confidence: 95%
See 1 more Smart Citation
“…Some of the research on UCS, however, does point to negative correlates of consenting to unwanted sex and highlights the importance of better understanding vulnerability factors associated with UCS. Among a sample of Italian heterosexual women, Scappini and Fioravanti (2022) found that the frequency of UCS was negatively correlated with sexual functioning and positively correlated with depression and anxiety. In a U.S. sample of individuals who identified as lesbian, gay, bisexual, transgender, or queer, who were in polyamorous relationships, and/or who were practitioners of bondage, domination, and sadomasochism (BDSM), Rubinsky (2020) found that engaging in UCS in the current relationship was negatively associated with mental health in the past 30 days.…”
Section: Why Ucs Mattersmentioning
confidence: 95%
“…Because there is an expectation within traditional scripts that women will subjugate their own sexual wants and desires, sexual script theory is most often evoked in the UCS literature to explain why women engage in UCS (e.g., Katz & Schneider, 2015; Kennett et al, 2013; Walker, 1997). In a direct test of the relationship, Scappini and Fioravanti (2022) found that endorsement of beliefs consistent with a traditional heterosexual script was correlated with women’s engagement in UCS. Although it is researched less, this same script could also explain men’s UCS if men feel that they must consent to—or even initiate—unwanted sex to prove that they have the expected level of masculine sexual desire.…”
Section: Sexual Script Theorymentioning
confidence: 99%
“…The copyright holder for this preprint this version posted June 13, 2024. ; https://doi.org/10.1101/2024.06.12.24308863 doi: medRxiv preprint traditional scripts offers guidance, predictability, and clarity but may carry potential drawbacks for both women and men. Women may experience discomfort initiating sexual activity, feel responsible to hold the role of the "gate-keeper" by delaying the first sexual encounter to occur with a new partner, and limit the expression of their sexual desires and boundaries [11][12][13].…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Further, women are believed to be more relationship-oriented when it comes to sexual motives, whereas societal perceptions often depict men as more sexually agent and pleasurefocused [11][12][13]. For men, script adherence may lead to performance pressure and restricted emotional expression.…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…The majority of women involved in such cases are adamant that their participation was and is: (1) completely voluntary—that is, consensual or even proactive; (2) claim that power asymmetries and gender norms (e.g., around age or conflicts of interests) did not play a distorting role; and (3) are offended by the suggestion that they were naïve or taken advantage of. Concerns around autonomy, fairness, and impartiality are often acknowledged and addressed by highlighting successful completion of the program and presence of robust individual sexual autonomy reflecting “sexual body‐esteem, sexual desire and pleasure, and sexual self reflection” (Horne & Zimmer‐Gembeck, 2005, 28; Scappini & Fioravanti, 2022).…”
Section: Composite Casementioning
confidence: 99%